Acute lung injury - from pathophysiology to treatment - Mokrá, D (Physiological research, 2020)
Acute lung injury is characterized by acute respiratory insufficiency with tachypnea, cyanosis refractory to oxygen, decreased lung compliance, and diffuse alveolar infiltrates on chest X-ray. The 1994 American-European Consensus Conference defined "acute respiratory distress syndrome, ARDS" by acute onset after a known trigger, severe hypoxemia defined by PaO2/FiO2</=200 mm Hg, bilateral infiltrates on chest X-ray, and absence of cardiogenic edema. Milder form of the syndrome with PaO2/FiO2 between 200-300 mm Hg was named "acute lung injury, ALI". Berlin Classification in 2012 defined three categories of ARDS according to hypoxemia (mild, moderate, and severe), and the term "acute lung injury" was assigned for general description or for animal models. ALI/ARDS can originate from direct lung triggers such as pneumonia or aspiration, or from extrapulmonary reasons such as sepsis or trauma. Despite growing understanding the ARDS pathophysiology, efficacy of standard treatments, such as lung protective ventilation, prone positioning, and neuromuscular blockers, is often limited. However, there is an increasing evidence that direct and indirect forms of ARDS may differ not only in the manifestations of alterations, but also in the response to treatment. Thus, individualized treatment according to ARDS subtypes may enhance the efficacy of given treatment and improve the survival of patients.
Keywords: akutní poškození plic; umělé dýchání; Acute Lung Injury; zvířata; Humans; Respiratory Distress Syndrome; syndrom dechové tísně; lidé; Respiration, Artificial; Animals